From personal benefits to green motives: consumer segments for targeted sustainability transitions in workplace canteens - Eg, Ragnhild; Gonera, Antje; Grini, Ida Synnøve; Pedersen, Mads Erling; Varela, Paula (Frontiers in Sustainability, 2025)
This study came to life through a collaboration between researchers and the service and food industries, aiming for nuanced consumer insights that may inform future sustainability interventions in workplace canteens. The study applied a mixed-methods approach to evaluate consumers’ attitudes, motives, and preferences within the canteen setting and with respect to the sustainability of food choices. Analyses of the quantitative data identified three distinct consumer segments that demonstrate the variability of consumers in food preferences and sustainability orientations. One segment was motivated by personal benefits, a second by both benefits and consideration for animal welfare, and a third was more markedly oriented toward sustainability. The qualitative analyses contributed additional viewpoints on feasible and desirable changes to canteen menus and operations. Combined, the findings highlight the necessity for canteens to consider the diversity of their clients and adopt versatile strategies tailored to distinct motives and preferences. This can in turn transform the canteen into an arena for testing sustainability interventions, yielding further insight into the efficacy of a range of means. The ambition is to extend outcomes of canteen interventions to other arenas, commencing with the household and culminating with society at large.